2017
DOI: 10.1186/s12955-017-0602-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of preterm birth <37 weeks on parents and families: a cross-sectional study in the 2 years after discharge from the neonatal intensive care unit

Abstract: BackgroundLittle is known about the quality of life of parents and families of preterm infants after discharge from the neonatal intensive care unit (NICU). Our aims were (1) to describe the impact of preterm birth on parents and families and (2) and to identify potentially modifiable determinants of parent and family impact.MethodsWe surveyed 196 parents of preterm infants <24 months corrected age in 3 specialty clinics (82% response rate). Primary outcomes were: (1) the Impact on Family Scale total score; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 57 publications
2
74
0
8
Order By: Relevance
“…True to our findings, taking care of a preterm baby together with other children can create relationship issues (Aagaard et al, 2015), causing a mother to withdraw from her professional career and cause social isolation (Lakshmanan et al, 2017;Murdoch & Franck, 2012). Families need time to adapt to their new responsibilities and daily routines, requesting support to do so (Bowles, 2016).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…True to our findings, taking care of a preterm baby together with other children can create relationship issues (Aagaard et al, 2015), causing a mother to withdraw from her professional career and cause social isolation (Lakshmanan et al, 2017;Murdoch & Franck, 2012). Families need time to adapt to their new responsibilities and daily routines, requesting support to do so (Bowles, 2016).…”
Section: Discussionmentioning
confidence: 72%
“…Hospitalization in the NICU reduces the interaction between a mother and her child and it affects their bond after discharge (Fleury, Parpinelli & Makuch, 2014). According to Lakshmanan et al (2017), extremely preterm infants' families constantly deal with chronic diseases and daily medical procedures, which have a negative impact on their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Prematurely born neonates are more likely to have increased health-related and neurodevelopmental delays including increased mental health risks for anxiety, depression and even more serious psychosis that can last a lifetime (Blencowe et al, 2013;D'Agata, Young, Cong, Grasso, & McGrath, 2016;Singh, Kenney, Ghandour, Dogan, & Lu, 2013). Quality of life for parents is also negatively impacted because of emotional stress, depression, acute and post-traumatic stress disorder (PTSD), physical fatigue, marital distress, as well as increased medical insurance needs and costs for out-of-pocket expenses (Blencowe et al, 2013;Hodek, von der Schulenburg, & Mittendorf, 2011;Lakshmanan et al, 2017). Readmissions of preterm infants to pediatric hospitals after initial discharge are costly as well and comprise a substantial proportion of all readmissions in children with medical complexities (Hudson, 2013;Kuzniewicz, Parker, Schnake-Mahl, & Escobar, 2013).…”
Section: Prematurity-associated Burden On Infants Families and Societymentioning
confidence: 99%
“…It should be emphasized that this factor combined with a poor public transport system and long distances from the follow-up service may constitute additional barriers to non-follow-up. Findings from national and international studies have indicated that families with lower purchasing power tend to discontinue follow-up of their children 6,18,[23][24] .…”
Section: Discussionmentioning
confidence: 99%